2018
DOI: 10.1016/j.solener.2017.11.023
|View full text |Cite
|
Sign up to set email alerts
|

History and trends in solar irradiance and PV power forecasting: A preliminary assessment and review using text mining

Abstract: Text mining is an emerging topic that advances the review of academic literature. This paper presents a preliminary study on how to review solar irradiance and photovoltaic (PV) power forecasting (both topics combined as "solar forecasting" for short) using text mining, which serves as the first part of a forthcoming series of text mining applications in solar forecasting. This study contains three main contributions: (1) establishing the technological infrastructure (authors, journals & conferences, publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
164
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(203 citation statements)
references
References 306 publications
(246 reference statements)
0
164
0
3
Order By: Relevance
“…Grubert [212] investigated the Life Cycle Assessment (LCA) literature by applying unsupervised topic modeling to more than 8200 environment-related LCA journal article titles and abstracts published between 1995 and 2014. Yang et al [213] mined 1000 abstracts from the Google Scholar database for search results for technology infrastructure of solar forecasting, classified the concepts of solar forecasting on the full texts of 249 papers from Science Direct, and also undertook the keyword analysis and topic modeling on six handpicked papers on emerging technologies related to the subject. Moro et al [214] performed text mining over the whole textual contents of papers, excluding only the references and authors' affiliations, published in a tourism-related journal from 1996 to 2016.…”
Section: Published Articlesmentioning
confidence: 99%
“…Grubert [212] investigated the Life Cycle Assessment (LCA) literature by applying unsupervised topic modeling to more than 8200 environment-related LCA journal article titles and abstracts published between 1995 and 2014. Yang et al [213] mined 1000 abstracts from the Google Scholar database for search results for technology infrastructure of solar forecasting, classified the concepts of solar forecasting on the full texts of 249 papers from Science Direct, and also undertook the keyword analysis and topic modeling on six handpicked papers on emerging technologies related to the subject. Moro et al [214] performed text mining over the whole textual contents of papers, excluding only the references and authors' affiliations, published in a tourism-related journal from 1996 to 2016.…”
Section: Published Articlesmentioning
confidence: 99%
“…Recent research has suggested that partial differential equation (PDE) fluid models can aid in cloud forecasting [24]. While three-dimensional PDE simulations can be computationally burdensome, there may be promise in the discovery of a suitable two-dimensional PDE model that operates in the photographic image spatial domain, using the method of Sparse Identification of Nonlinear Dynamics (SINDy) [3].…”
Section: Future Workmentioning
confidence: 99%
“…The combination of different forecast methods has been recently identified as an essential trend in solar forecasting (Yang et al, 2018). The downscaling procedure presented herein is a simple example of such a combination.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…For intrahour forecasting, machine learning methods or on site cloud tracking methods have been developed, while for more than six hours ahead and day ahead forecasts, Numerical Weather Prediction (NWP) forecasts are generally used as the primary source of information (Mathiesen et al, 2013;Thorey et al, 2015). Using satellite images provides information on horizontal cloud structures and has proven to be efficient for the intraday horizon (see the recent review by Yang et al, 2018). The widely studied cloud motion vector methods (Hammer et al, 1999;Lorenz et al, 2004;Escrig et al, 2013) estimate a motion field from successive cloud satellite images and produce a forecast by advecting the clouds.…”
Section: Introductionmentioning
confidence: 99%